Risk factor analysis for long-term unfavorable ocular outcomes in children treated for retinopathy of prematurity - Mutlu, Fatih Mehmet; Küçükevcilioğlu, Murat; Ceylan, Osman Melih; Altınsoy, Halil Ibrahim; Sarıcı, S Umit (The Turkish Journal of Pediatrics, 2013)
The aim in this study was to report long-term ocular outcomes of neonates treated for retinopathy of prematurity (ROP) and potential risk factors for unfavorable ocular outcomes. The study consisted of neonates treated for ROP between March 1999 and November 2009. Data relating baseline characteristics and late structural, functional and refractive ocular outcomes were recorded. The association between the unfavorable ocular outcomes and ROP-related risk factors was evaluated by regression analysis. Forty-eight children were included for assessment. Average chronological age at the time of followup was 3.11±0.73 years. The rates of unfavorable structural and functional outcomes were 12% and 15.3%, respectively. Ocular deviation was common (27.1%), and mostly esotropic (12/13). A clear myopic tendency was observed (51.2%), and the mean spherical equivalent per eye was -0.72±2.9 diopters. Regression analyses for unfavorable ocular outcomes revealed intraventricular hemorrhage as a core independent risk factor. In conclusion, ROP treatment has shown promising results in both structure and function. Because of the high risk of developing an unfavorable outcome, a more intense follow-up is required in neonates with a history of intraventricular hemorrhage in the neonatal period. Further studies from other centers are needed to develop a national database, which may validate this observation.